The impact of ECB communication on financial market expectations - Michael J. Lamla; Sarah M. Rupprecht (ETH Zurich, KOF Swiss Economic Institute, 2006)
This paper analyzes European financial markets' comprehension and interpretation of ECB communication signals. By applying a novel indicator developed by Berger et al. (2006), that quantifies the contents of the ECB's introductory statements, we find that communication affects the term structure of interest rates in the medium run over a horizon between five months to one year. Our results suggest that financial market agents expect the ECB to prepare them for a change in interest rates well in advance. However, judging upon the dynamics of the response, the exact timing of a decision is less foreseeable. Disentangling the effects of ECB statements on prices, the real and the monetary sector, we provide evidence that especially the ECB's interpretation and forecasts of price developments represent important news to financial market agents.
Keywords: E43; E44; E58; 330; Central Bank Communication; Expectations; Term Structure of Interest Rates; Yield Curve; ECB; Zentralbank; Öffentlichkeitsarbeit; Informationsverbreitung; Zinsstruktur